The Impact of Forest Plantation Thinning on Flying Insect Community in Sukabumi Forest Management Unit - Ali Akbar; Ahmad Budiaman; Noor Farikhah Haneda (Media Konservasi, 2019)
Insects are part of the forest ecosystem that plays an important role in the sustainability of the ecological functions of the forest plantations. The purpose of this study was to analyze the effect of thinning on insect communities and determine the types of insects which has potential to be bioindicators in order to assess the success of thinning in forest plantations. This research was conducted on forest plantation at the part of Forest Management Unit (BKPH) Cikawung and West Gede, Forest Management Resort (RPH) Ciguha, Forest Management Unit (KPH) Sukabumi Perum Perhutani Regional Division III West Java and Banten. The plot used in this research is a circular plot with a radius of 17.95 m. The traps used are malaise traps that is spread on thinning blocks at thinning intensity of 20%. The type of stand of thinning plots is Pinus merkusii in the age class 3. The obtained insects later identified to the morphospecies level. The results of the study show that thinning affect changes in environmental conditions and insect composition. In thinning blocks, there was decrease in the number of insect compositions by 11 families, 4 genera and also decrease of 3 morphospecies. Overall, thinning activities have no effect on changes over species richness index and evenness index of insect species. Diptera is a type of insect that can be used as a bioindicator, it states based on the consideration of ease in obtaining information related to taxonomy and biological properties, ease of identification, role of the ecosystem, pressure status and abundance parameters. Keywords: bioindicator, ecological assessment, forest disturbance